Disclosing The Conduct of Using E-Money In Semarang City - Aji Muhammad Nur Arifin; Eviatiwi Sugiyanto (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study is to reveal the behavior of using e-money in Semarang City and its supporting and barriers factors. This research uses qualitative methods, with a case study approach. In this study, the selected informants were employees of PT Bank Mandiri (Persero) Tbk, customers, and expert informants in the field of marketing. From the research results, it is known that the strongest supporting factor in using e-money is the perception of convenience among other factors. For the most common barriers factor is the risk of losing the card. Then the formation of its own behavior begins with a mix of promotions and needs so that a perception of convenience appears, a perception of benefits so that an interest in using arises e-money